Recognition and Management of Postpartum Hemorrhage - Tasabih Ali EL Hassan Mohamed; Edwin Chandraharan; Yang Pan (Maternal-Fetal Medicine)
Abstract. Postpartum hemorrhage (PPH) is an obstetric emergency and refers to excessive blood loss after birth. Loss of blood volume and oxygen-carrying capacity may lead to maternal hypovolemia and hypotension resulting in tissue hypoxia, the onset of anaerobic metabolism, and multiorgan failure. If timely and appropriate action is not taken, cardiac arrest and maternal death may occur. If the amount of blood loss exceeds 500 mL following a vaginal birth or 1000 mL during or following a cesarean section, it is termed PPH. Similar to any other surgical hemorrhage, PPH is classified into primary PPH (occurs within 24 hours of birth) or secondary PPH (between 24 hours and 12 weeks postpartum). PPH is a major contributor to maternal deaths worldwide, and it is estimated that a person dies because of PPH approximately every 5 minutes. Therefore, measures should be directed at prevention and early detection of PPH with prompt management. The prevalence of PPH varies globally and is influenced by location, socioeconomic factors, and the availability and quality of health care. The World Health Organization reported that PPH accounts for a quarter of global maternal deaths. The Mothers and Babies Reducing Risks through Audits and Confidential Enquiries report from the United Kingdom (2023) highlighted that despite rare mortality due to hemorrhage, the number of people dying of obstetric hemorrhage is not decreasing, particularly among people with abnormally invasive placentation. Additionally, substandard care was found to be responsible for more than 50% of deaths due to PPH in the United Kingdom. Therefore, it is vital that adequate healthcare infrastructure, trained and competent healthcare professionals, and immediate access to resources, interventions, and multidisciplinary teams are essential both in well-resourced and resource-restrained healthcare systems. Healthcare professionals must identify the potential risk factors for PPH and initiate preventive measures whenever possible. Additionally, they must respond swiftly if PPH occurs and ensure a multidisciplinary, multilayered approach for a synchronized response to optimize outcomes. This review article emphasizes the etiopathogenesis, diagnosis, and management of PPH based on current scientific evidence as well as international best practice recommendations.